The Palgrave Handbook of Critical Physical Geography (Springer International Publishing, 2018)
This handbook is recognition of the need to better integrate physical and human geography. It combines a collection of work and research within the new field of Critical Physical Geography, which gives critical attention to relations of social power with deep knowledge of a particular field of biophysical science. Critical Physical Geography research accords careful attention to biophysical landscapes and the power relations that have increasingly come to shape them, and to the politics of environmental science and the role of biophysical inquiry in promoting social and environmental justice. The Palgrave Handbook of Critical Physical Geography lays out the scope and guiding principles of Critical Physical Geography research. It presents a carefully selected set of empirical work, demonstrating the range and intellectual strength of existing integrative work in geography research. This handbook is the first of its kind to cover this emerging discipline and will be of significant interest to students and academics across the fields of geography, the environment and sustainability. .